2022
DOI: 10.1093/molbev/msac121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Reproductive Investment Across an Ephemerality Gradient inDaphnia pulex

Abstract: Species across the tree of life can switch between asexual and sexual reproduction. In facultatively sexual species, the ability to switch between reproductive modes is often environmentally dependent and subject to local adaptation. However, the ecological and evolutionary factors that influence the maintenance and turnover of polymorphism associated with facultative sex remain unclear. We studied the ecological and evolutionary dynamics of reproductive investment in the facultatively sexual model species, Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 141 publications
(186 reference statements)
0
16
0
Order By: Relevance
“…We assessed whether the maternal environment affected the early hatching rate as a function of mesocosm age. Over the 8 sample weeks, the density of individuals increased from 60 individuals to several thousand (Barnard-Kubow et al, 2022). To assess the early hatching rate of the two clonal lineages, we collected ephippia weekly from the mesocosms, and found that the rate of early hatching increased as mesocosms became older (df= 1, χ 2 =34.03 p=5.434e-09, Fig 1B, Model 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed whether the maternal environment affected the early hatching rate as a function of mesocosm age. Over the 8 sample weeks, the density of individuals increased from 60 individuals to several thousand (Barnard-Kubow et al, 2022). To assess the early hatching rate of the two clonal lineages, we collected ephippia weekly from the mesocosms, and found that the rate of early hatching increased as mesocosms became older (df= 1, χ 2 =34.03 p=5.434e-09, Fig 1B, Model 1).…”
Section: Resultsmentioning
confidence: 99%
“…D. pulex were collected from a semi-permanent pond in Dorset, England in the Kilwood Nature Reserve (50.64, - 2.09) in the spring of 2017. Pond ephemerality was determined using trail cameras, and multi-year survey of the genetic composition of D. pulex (Barnard-Kubow et al, 2022). Live Daphnia samples were transported back to the University of Virginia, where clonal lineages were established from wild female isolates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we show that North American and European D. pulex possess tens of thousands of shared polymorphisms, whose abundance cannot be explained by incomplete lineage sorting, Leinonen et al, 2011). We incorporated wild-sequenced or isogenic female lineages (Barnard-Kubow et al, 2022;Lynch et al, 2017;Xu et al, 2015;Ye et al, 2022), and excluded samples that were from mutation accumulation studies. Species identity for these samples was based on annotations provided in each SRA record.…”
mentioning
confidence: 99%